2022
DOI: 10.1111/pde.14994
|View full text |Cite|
|
Sign up to set email alerts
|

Successful treatment of a child's pityriasis rubra pilaris (PRP) with ustekinumab and acitretin

Abstract: Pityriasis rubra pilaris (PRP) is a rare inflammatory skin disease that occurs with phenotypic variability in adults of all ages as well as in children. Data on the treatment of PRP is limited. Here, we report a 5‐year‐old girl with widespread skin involvement and prominent palmoplantar hyperkeratosis who was initially treated for psoriasis. After reevaluation, a diagnosis of PRP was made, and the patient had an excellent therapeutic response to ustekinumab and acitretin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A recent systematic review identified that biologic treatment was successful in 81.1% of the patients when used as monotherapy or combination therapy with existing treatments [ 7 , 11 ]. Recent case reports demonstrated the effectiveness of the combination of ustekinumab, an IL-12 and IL-23 inhibitor, with acitretin, in clearing keratoderma within the classic adult, pediatric, and refractory PRP [ 5 , 10 ]. Another systematic review demonstrated that infliximab was associated with a more rapid response than etanercept.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review identified that biologic treatment was successful in 81.1% of the patients when used as monotherapy or combination therapy with existing treatments [ 7 , 11 ]. Recent case reports demonstrated the effectiveness of the combination of ustekinumab, an IL-12 and IL-23 inhibitor, with acitretin, in clearing keratoderma within the classic adult, pediatric, and refractory PRP [ 5 , 10 ]. Another systematic review demonstrated that infliximab was associated with a more rapid response than etanercept.…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review demonstrated that infliximab was associated with a more rapid response than etanercept. On the other hand, ustekinumab monotherapy, or in combination with other regimens, has been proven to give long-term control in treating adult and juvenile PRP [ 5 , 10 ]. A few case reports have also shown clearance of palmoplantar keratoderma in types 1 and 2 PRP within two weeks of using secukinumab [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these patients responded positively to this treatment. One patient, a 17-year-old boy previously treated with oral corticosteroids, phototherapy, acitretin and cyclosporine, did not respond to etanercept therapy but achieved disease remission with adalimumab [ 30 – 39 ]. Here, we have demonstrated a good efficacy and safety profile of risankizumab among pediatric patients with PRP.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-17 inhibitors and ustekinumab, a combined interleukin-12 and interleukin-23 inhibitor, have shown promising results in several case reports. [1][2][3] In particular, ustekinumab is emerging as a potential first-line treatment for the subgroup of patients with CARD14 variants. 4 CARD14 variants are seen as a predisposing factor to autoinflammatory keratinization, as seen in juvenile PRP.…”
mentioning
confidence: 99%